(untitled) (KULT_online, 2014)
By taking into account various theoretical, methodological and ideological debates, Andrea Kirchknopf situates the contemporary phenomenon of post-Victorianism within its political, social, cultural, and economic contexts. Thus she makes this field of research, which is focussed on studying contemporary re-imaginings of the 19th century, accessible to a wider audience and provides a carefully compiled introduction to this topic. The rewritings analysed in her book are regarded as narratives of identity and are directly placed within the respective theoretical surveys of the literary scene and other discourses and contexts, where they serve as illustrative examples.